Analisis Penggunaan Aplikasi Poinku sebagai Daya Tarik dan Fasilitas Belanja di Indomaret Sulursari Kec. Gabus Kab. Grobogan - Rahmawati, Siti Umi; Ismanto, Bambang; Permatasari, Carolina Lita (Fakultas Ekonomi Universitas Samudra, 2023)
The study aims to determine the use of the Poinku application as an attraction and shopping facility at Indomaret Sulursari, Gabus District, Grobogan Regency, Central Java Province. Research using descriptive qualitative method. The informants consisted of 11 participants, both users and non-users of the Poinku application. Data obtained through observation, interviews and documentation, by testing the validity of the data using triangulation. The results of the study show that the Poinku application attracts consumers in making purchases, especially with facilities such as promotions and points because it attracts consumers to make repeat purchases. Promotional factors through the Poinku application have an important impact on consumers as a strategy to increase purchases